2006
DOI: 10.1007/s10754-006-6862-9
|View full text |Cite
|
Sign up to set email alerts
|

OBRA 1987 and the quality of nursing home care

Abstract: Because minimum government standards for quality regulate only part of the market failure, they may have unintended effects. We present a general theory of how government regulation of quality of care may affect different market segments, and test the hypotheses for the nursing home market. OBRA 1987 was a sweeping government reform to improve the quality of nursing home care. We study how the effect of OBRA on the quality of nursing home care, measured by resident outcomes, varied with nursing home profitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…For example, home health care quality measures were recently released by the Centers for Medicare and Medicaid Services http://www.medicare.gov/hhcompare/home.asp and could be useful in the context of informal care. Alternatively, one could adapt measures from outcome-based measures of nursing home quality such as acquired pressure sores [27], use of restraints [27,28] or urinary tract infections [29]. Finally, indirect measures of quality of caregiving (e.g., care recipient's receipt of annual flu shots [30]) could also be useful.…”
Section: Discussionmentioning
confidence: 99%
“…For example, home health care quality measures were recently released by the Centers for Medicare and Medicaid Services http://www.medicare.gov/hhcompare/home.asp and could be useful in the context of informal care. Alternatively, one could adapt measures from outcome-based measures of nursing home quality such as acquired pressure sores [27], use of restraints [27,28] or urinary tract infections [29]. Finally, indirect measures of quality of caregiving (e.g., care recipient's receipt of annual flu shots [30]) could also be useful.…”
Section: Discussionmentioning
confidence: 99%
“…The nursing home market is one of the most highly regulated markets in the United States (Kumar, Norton, & Encinosa, 2006; X. Zhang & Grabowski, 2004).…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…OBRA-87 undoubtedly changed nursing home care in many ways. Some empirical research has attributed OBRA-87 as successfully influencing quality (Shea, Russo, & Smyer, 2000), whereas some studies have identified a relatively small influence on quality (Kumar, Norton, & Encinosa, 2006). However, OBRA-87 was a watershed event in ways other than its influence on quality.…”
Section: Policy Initiatives and Qualitymentioning
confidence: 99%